Breast-feeding and hospitalization for asthma in early childhood: a nationwide longitudinal survey in Japan. Issue 10 (6th November 2014) - Yamakawa, Michiyo; Yorifuji, Takashi; Kato, Tsuguhiko; Yamauchi, Yoshitada; Doi, Hiroyuki
Abstract: Objective: Whether or not breast-feeding is protective against asthma among children is still controversial. Therefore, we examined the effects of breast-feeding on hospitalization for asthma in early childhood. Design: Secondary data analyses of a nationwide longitudinal survey of children in Japan ongoing since 2001, with results collected from 2001 to 2004. We used logistic regression models to evaluate the associations of breast-feeding with hospitalization for asthma in children between the ages of 6 and 42 months, adjusting for children's factors (sex, day-care attendance and presence of older siblings) and maternal factors (educational attainment and smoking habit). Setting : All over Japan. Subjects: Term singleton children with information on feeding practices during infancy ( n 43367). Results: After adjusting for maternal factors and children's factors, exclusive breast-feeding at 6–7 months of age was associated with decreased risk of hospitalization for asthma in children. The adjusted odds ratio was 0·77 (95 % CI 0·56, 1·06). One-month longer duration of breast-feeding was associated with a 4 % decreased risk of hospitalization for asthma (OR=0·96; 95 % CI 0·92, 0·99). Conclusions: The protective effects of breast-feeding on hospitalization for asthma were observed in children between the ages of 6 and 42 months.